Karakteristik Campuran Stone Matrix Asphalt Kasar dengan Bahan Tambah Kadar Ban Bekas - Diki Bangngalino; Rais Rachman; Alpius (Paulus Civil Engineering Journal, 2022)
This study aims to determine the characteristics of a mixture of coarse Stone Matrix Asphalt with the addition of used rubber, as well as to determine the effect of adding prohibited rubber to a mixture of coarse Stone Matrix Asphalt, which uses aggregates from the Sa'dan River, Sesean District, North Toraja. The method in this study is Marshall Conventional to obtain the characteristics of Coarse Asphalt Matrix Stone. The test results of characteristics, asphalt characteristics, and specific gravity of the filler meet the requirements for road pavement materials. The results of the mixed characteristics of the Coarse Asphalt Stone Matrix, namely Stability, Flow, VIM and VMA, all meet the General Specifications of Highways 2018 with a minimum limit of 90%.